Feminism, the public and the private - Landes, Joan B., 1946- (Oxford readings in feminism., 1998)
"This latest volume in the Oxford Readings in Feminism series presents the results of the multi-disciplinary feminist exploration of the distinction between public and private. Contributors demonstrate the significance of the distinction in feminist theory, its articulation in the modern and late modern public sphere, and its impact on identity politics within feminism in recent years. Feminism, the Public and the Private offers an essential perspective on feminist theory for students and teachers of women's and gender studies, cultural studies, history, political theory, geography and sociology."--Publisher description